Tráfico de animais silvestres : limites e possibilidades de atuação dos órgãos competentes - Rehbein, Katiele Daiana da Silva (2023)
Wild animal trafficking is one of the most profitable illegal activities in the world, being considered the third largest illegal activity on Earth, surpassed only by drug and weapons trafficking. This crime is committed by anyone who captures animals from nature, transports them and/or keeps them in captivity with the intention of making money; therefore, anyone who is involved in the trade and/or any of its phases, selling or even buying these animals is committing a crime and is part of this illegal network. In this context, the present dissertation aims at analyzing the deficiencies and alternatives for the agencies to be more effective in combating this illicit trade, seeking results to the following research problem: What are the limits and possibilities of action to combat wildlife trafficking in Brazil by the competent agencies, with regard to the Federal and State spheres? To this end, initially, a bibliographic survey of the main aspects related to the theme was carried out, among which the conceptualization of this type of animal trade, the relevant legislation, and its consequences, such as the risk to the Brazilian biodiversity; as well as a treatise on birds as the most trafficked animals in Brazil. In a second moment, seeking to understand the factors and limits of the fight against the illicit trade in Brazil, qualitative and quantitative data were analyzed, with an exploratory and descriptive nature, being this the methodological approach of the research. Besides this, the bibliographical research was used as a procedure, with document analysis and the application of a data collection instrument. Content analysis was performed, as a technique for data treatment, for the qualitative diagnosis of the final reports of the Courses/Workshops on Combating Trafficking in Wild Animals and for the questionnaires applied, both of which counted on the participation of agents of public agencies linked to the containment of crime; and descriptive analysis, also as a technique for quantitative data treatment of the questionnaires. As answers, from the data and information gathered, it was possible to understand some of the main barriers to curb the illicit act, such as the lack of integration among agencies, the insufficiency of the law, multiplicity of subsystems to collect and store information/data, and also the lack of training of surveillance agents and lack of environmental education of the population. Some emerging solutions followed the line of changing the law, increasing the criminal/administrative penalties and typifying the crime, creating a unified system with access to all active public agencies, and measures to have more integration between these agencies.